Main bronchus location is a predictor for metastasis and prognosis in lung adenocarcinoma: A large cohort analysis. (June 2018) - Yang, Lin; Wang, Shidan; Gerber, David E.; Zhou, Yunyun; Xu, Feng; Liu, Jiewei; Liang, Hao; Xiao, Guanghua; Zhou, Qinghua; Gazdar, Adi; Xie, Yang
Highlights: Main bronchus adenocarcinomas have worse prognosis than the non-main bronchus ones. Main bronchus adenocarcinomas have a higher rate of lymph node involvement. Main bronchus adenocarcinomas have a higher rate of distant metastasis. Main bronchus location is an independent predictor of worse outcomes. Abstract: Objectives: In the literature, inconsistent associations between the primary locations of lung adenocarcinomas (ADCs) with patient prognosis have been reported, due to varying definitions for central and peripheral locations. In this study, we investigated the clinical characteristics and prognoses of ADCs located in the main bronchus. Methods: A total of 397, 189 lung ADCs registered from 2004 to 2013 in the National Cancer Database (NCDB) were extracted and divided into main bronchus-located ADCs (2.5%, N = 10, 111) and non-main bronchus ADCs (97.5%, N = 387, 078). The ADCs located in the main bronchus and those not in the main bronchus were compared in terms of patient prognosis, lymph node involvement, distant metastases and other clinical features, including rate of curative-intent resection, histologic grade, and stage. Results: ADCs located in the main bronchus had significantly worse patient survival than those in the non-main bronchus, both for all patients (HR = 1.82, 95% CI 1.78–1.86) and for those undergoing curative-intent resection (HR = 2.49, 95% CI 2.23–2.78). Furthermore, ADCs located in the main bronchus had a significantly higher rate of lymph node involvement and distant metastasis than those not in the main bronchus, when stratified by tumor size (trend test, p < e −16 ). Multivariate analysis of overall survival showed that main bronchus location is a prognostic factor (HR = 1.15, 95% CI 1.08–1.23) independent of other clinical factors. Conclusions: Main bronchus location is an independent predictor for metastasis and worse outcomes irrespective of stage and treatment. Tumor primary location might be considered in prognostication and treatment planning.